PREDIKSI KADAR FLAVONOID TOTAL TEMPUYUNG (Sonchus arvensis L.) MENGGUNAKAN KOMBINASI SPEKTROSKOPI IR DENGAN REGRESI KUADRAT TERKECIL PARSIAL - E. Rohaeti; R. Heryanto; M. Rafi; A. Wahyuningrum; L. K. Darusman (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2011)
The potency of Fourier transformed infrared spectroscopy (FTIR) combined with chemometric method for determining the total flavonoid content of tempuyung (Sonchus arvensis L) has been investigated. Partial least squares regression (PLSR) was used to build a prediction model based on the relationship between concentration of total flavonoids obtained from the reference method (AlCl3) and FTIR spectrum. Application of PLSR in the determination of total flavonoids content in tempuyung gave moderate value for goodness of fit of the model with r calibration = 0974, r validation = 0742, Standard Error Calibration = 0023, Root Mean Square Error Calibration = 0023, Standard Error Prediction = 0078, Root Mean Square Prediction Error = 0076, and bias = -0001 using FTIR derivative spectrum segment 1. From these results, combination of FTIR spectrum and PLSR can be used for the prediction of total flavonoids content in tempuyung.